Vitamin D Receptor Deletion Leads to the Destruction of Tight and Adherens Junctions in Lungs. Issue 4 (2nd October 2018) - Chen, Honglei; Lu, Rong; Zhang, Yong-guo; Sun, Jun
ABSTRACT: Vitamin D deficiency has been linked to various inflammatory diseases in lungs, including pneumonia, asthma and chronic obstructive pulmonary disease. However, the mechanisms by which vitamin D and vitamin D receptor reduce inflammation in lung diseases remain poorly understood. In this study, we investigated the expression and cell-specific distribution of tight and adherens junctions in the lungs of vitamin D receptor-deficient (VDR -/- ) mice. Our results demonstrated that mRNA and protein levels of claudin-2, claudin-4 and claudin-12 were significantly decreased in the lungs of VDR -/- mice. Other tight and adherens junction proteins, such as ZO-1, occludin, claudin-10, β-catenin, and VE-cadherin, showed significant differences in expression in the lungs of VDR -/- and wild-type mice. These data suggest that altered expression of tight and adherens junction molecules, especially of claudin-2, −4, −10, −12, and −18, after chronic pneumonia caused by VDR deletion could increase lung permeability.Therefore, VDR may play an important role in maintaining pulmonary barrier integrity. Further studies should confirm whether vitamin D/VDR is beneficial for the prevention or treatment of lung diseases.